The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.5005/jp-journals-10024-1116
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Temporomandibular Disorders in Iranian Dental and Nondental Students

Abstract: Aim The aim of this study was to define the prevalence and severity of temporomandibular disorders (TMD) among Iranian dental and nondental students who attended Shiraz University of Medical Sciences. Materials and methods The samples consisted of 200 subjects, 100 dental and 100 nondental students (equal distribution between males and females). Subjects ages ranged from 18 to 30 years (24.07 ± 2.93). A functional evaluation was performed using the Helkimo dysfunction index (Di). Data were evaluated by the C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 27 publications
1
19
0
Order By: Relevance
“…The reported prevalence TMD in the present study is comparatively high, amounting to 77.2%. However, the reported prevalence of TMD among university student populations has been in the range of approximately 30%‐55%, with 71% in a single Iranian study …”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The reported prevalence TMD in the present study is comparatively high, amounting to 77.2%. However, the reported prevalence of TMD among university student populations has been in the range of approximately 30%‐55%, with 71% in a single Iranian study …”
Section: Discussionmentioning
confidence: 97%
“…The prevalence of TMD in this North Queensland dental school was comparatively higher to other university student populations. Although, the available data are limited to compare the prevalence of TMD symptoms between dental and non‐dental students, it appears that dentistry students have slightly higher tendency to have TMD symptoms …”
Section: Discussionmentioning
confidence: 99%
“…Oliveira et al, 15 Bagis et al, 16 Bahrani et al, 17 and Chuang. 18 However, other studies concluded that there were no significant differences between males and females.…”
Section: 5005/jp-journals-10024-1982mentioning
confidence: 99%
“…7,10,13 Many studies in other universities concluded that TMD is higher among medical students than other disciplines. 7,12,13,17 Hence, the aim of the current study was to assess the prevalence and severity of TMD among undergraduate medical students and to compare the severity of TMD between them in the presence of parafunctional habits, such as khat chewing.…”
Section: 5005/jp-journals-10024-1982mentioning
confidence: 99%
“…In a literature search, we found a few reports addressing the epidemiology of TMD in the Middle East, among which only a single study was found in a Jordanian population; however, it lacked the use of a standard protocol . Therefore, the present study was designed to document the prevalence of TMD signs and symptoms and potential correlations in a Northern Jordanian sample of participants using the DC/TMD protocol as the first of its kind in Jordan.…”
Section: Introductionmentioning
confidence: 99%